Experiência de adoecimento por adultos jovens com leucemia - Siqueira, Beluci Bianca Nunes de (2014)
This research aims at understanding the experience of illness in young adults with a chronic condition: the Acute Myeloid Leukemia. This study emphasize the social dimension, because this new condition is treated bad, mutilating, fatal prognosis; being compared / associated with physical, mental, and social disorders, moreover, detracts society people with cancer have fallen ill-branding them. This is a qualitative research based on assumptions of phenomenology of Alfred Schutz. Data were obtained through semi-structured interviews conducted with four youths, aged 20-28 years in the maintenance phase of treatment in an oncology referral from November 2013 until January 2014, the state of Mato Groso. After the interviews were performed description of the interviewees, and then grouping the main themes in the experiences of the diseased. The results include: the process of discovery of illness from leukemia, where the highlight is the diagnosis made quickly that being the difference between life and death; the concept, and the leukemia attributed to a fatal, contagious, silent and invisible disease; causal notions related to a disease with pluralistic causes according to its context, such as heredity, external agents and negatively striking moment in your life; impacts and everyday coping strategies reported most importance were linked with body appearance, experienced death of friends and harbingers of death itself and the social support received by both the informal and formal support for the completion of the treatment, and the motivations of the subjects for their actions. Research has demonstrated the complexity of chronic illness, such as illness marks the daily lives of the subjects and how the coping strategies in an attempt to integrate the new chronic condition pace of life are held, redefining his experience with leukemia. Furthermore, it allows to reflect on care practices and oncological management.